2008
DOI: 10.1158/1078-0432.ccr-07-1994
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Infiltrating Lymphocytes and Perforation in Colon Cancer Predict Positive Response to 5-Fluorouracil Chemotherapy

Abstract: Purpose: The major pathologic markers of prognosis in colorectal cancer include vascular invasion by tumor cells, invasion of adjacent lymph nodes, and perforation of the serosal wall. Recent work suggests that a high density of tumor-infiltrating lymphocytes (TIL) is associated with good outcome independently of these established prognostic markers. The aim of the present study was to investigate the prognostic significance of TILs and other routinely reported pathologic features in colon cancer, particularly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(71 citation statements)
references
References 20 publications
(28 reference statements)
3
66
0
2
Order By: Relevance
“…[24][25][26][27][28][29][30][31][32][33] As in this study, MSI tumors have previously been reported to have a higher degree of T-cell infiltration than MSS tumors. [35][36][37] Yet the potential confounding effect of MSI screening status on the prognostic importance of T-cell infiltration has been considered in only a minority of reports, of which most, 32,36,[39][40][41]46,53,54 but not all, 30,55 found that the better prognosis associated with dense T-cell infiltration was independent of MSI screening status.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…[24][25][26][27][28][29][30][31][32][33] As in this study, MSI tumors have previously been reported to have a higher degree of T-cell infiltration than MSS tumors. [35][36][37] Yet the potential confounding effect of MSI screening status on the prognostic importance of T-cell infiltration has been considered in only a minority of reports, of which most, 32,36,[39][40][41]46,53,54 but not all, 30,55 found that the better prognosis associated with dense T-cell infiltration was independent of MSI screening status.…”
Section: Discussionsupporting
confidence: 60%
“…Presence of peri-and intratumoral inflammatory cells has consistently been associated with a better prognosis in colorectal cancer. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Many of these reports have been based on routine hematoxylin and eosin stained tissue sections, but an increasing number of studies have used immunohistochemical markers such as the pan T-cell marker CD3. CD3 is a cell surface protein associated with the T-cell receptor.…”
mentioning
confidence: 99%
“…Our results were consistent with some other scholars. Previous reports have suggested that a high number of tumor infiltrating lymphocytes was strongly associated with good outcomes in the patients with colorectal cancer (Galon et al, 2006;Morris et al, 2008;Laghi et al, 2009;Cañadas-Garre et al, 2012). A recent study conducted by Kitayama et al (2011) showed the association of a high lymphocyte ratio in peripheral blood before and during preoperative radiotherapy in the patients of rectal cancer with a complete pathological response, suggesting the lymphocyte-mediated immune response plays an important role in the eradication of tumor cells by preoperative radiotherapy.…”
Section: Figure 1 Impact Of Pretherapeutic Lymphocyte Ratio On 5-yeamentioning
confidence: 94%
“…Il est par conséquent concevable que la nature de l'infiltration immunitaire au site tumoral (sa qualité, son intensité) puisse moduler la qualité de la réponse à ces thérapies. Le bénéfice de survie de patients atteints de CRC (colorectal cancer) ayant reçu une chimiothérapie à base de 5FU est grandement amélioré chez les patients qui présentent une forte infiltration de lymphocytes dans la tumeur (TIL) (p = 0,02) [32]. Étant donné que la présence de TIL reflète une réponse immunitaire adaptative, ces résul-tats suggèrent une interaction entre la réponse immunitaire et la chimiothérapie.…”
Section: Autres Marqueurs Associés à La Survie Des Patientsunclassified